2015
DOI: 10.1097/igc.0000000000000469
|View full text |Cite
|
Sign up to set email alerts
|

Economic Considerations on the Follow-Up Practice in Gynecologic Cancers

Abstract: There are few available lights in economic considerations on gynecologic cancer follow-up, represented by all the published studies, and many shadows that require to be clarified by properly designed randomized trials including cost-effectiveness analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It was concluded that the evidence in this area is poor due to low quality of available studies regarding study design and sample size [23]. The number of planned follow-up visits illustrates the intensity of post-treatment surveillance in a population of women at low risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that the evidence in this area is poor due to low quality of available studies regarding study design and sample size [23]. The number of planned follow-up visits illustrates the intensity of post-treatment surveillance in a population of women at low risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the evidence regarding the cost-effectiveness of follow-up procedures in gynecologic malignancies have been reviewed [23]. It was concluded that the evidence in this area is poor due to low quality of available studies regarding study design and sample size [23].…”
Section: Discussionmentioning
confidence: 99%